Design of Decision Support System in Determining Maintenance Priority Using Weighted Product (WP) Method - Setiawan, Puja Memo Dwi; Hardianto, Romi; Prawiro, Radius (Journal of Computer Scine and Information Technology, 2025)
Technological developments are very dynamic so that the information produced is fast and accurate, starting from an office to the educational level. Management of facility maintenance data at State Senior High School 2 Sijunjung is still done manually. Determining facility maintenance work based on manual management can cause the determination of facility maintenance work to be irrelevant. To overcome this problem, a decision support system is needed that can improve the process of managing and determining facility maintenance work using the Weighted Product (WP) method. The Weighted Product (WP) method is a multi-criteria decision-making method used to solve the problem of selecting the best option from several available alternatives. Based on the results of the analysis in the process of determining facility maintenance, the researcher made manual calculations using the weighted product method where there are 5 criteria and 15 alternatives. From the results of these calculations, the researcher made a decision by looking at the ranking of the WP calculation where the art room was ranked first with a value of 0.0900. This system is expected to be able to assist schools in managing facility data that affects the determination of facility maintenance work priorities and as a basis for decision-making in determining facility maintenance work